KETERKAITAN SEKTOR UNGGULAN DI PROVINSI ACEH: PENGARUHNYA TERHADAP PENGEMBANGAN PERKOTAAN - Muhammad Fazil; Muhammad Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study aimed to determine the leading sectors in the districts and cities in the province of Aceh as a guideline and a grounding in economic development planning in the region level. This study uses secondary data Gross Regional Domestic Product of 23 districts/cities in Aceh province and Gross Regional Domestic Product province of Aceh during 2009-2013. The analysis was using Shift Share Analysis Model and Pearson Correlation Matrix Model. From the analysis of The Shift Share Model and Pearson Correlation test results showed that The City of Sabang leading sectors have very strong relationship with the leading sectors in Banda Aceh City, and The Districts of Aceh Besar, Aceh Jaya, and Aceh Barat. The leading sectors of Banda Aceh has a very strong relationship with the City of Sabang, and The Districts of Aceh Besar and Aceh Barat. The City of Lhokseumawe leading sectors have a strong relationship with the districts of Pidie Jaya, Bener Meriah and Aceh Tengah. Leading sectors of Langsa City have strong relationship with The Districts of Aceh Tamiang and Aceh Tenggara. Leading sectors of Subulussalam have very strong relationship with the leading sectors in The Districts of Aceh Barat Daya, Aceh Selatan, Aceh Singkil, and Simeulue.Penelitian ini bertujuan menentukan sektor unggulan pada kabupaten dan kota di Provinsi Aceh sebagai suatu pedoman dan landasan dalam perencanaan pembangunan ekonomi di daerah. Penelitian ini menggunakan data sekunder Produk Domestik Regional Bruto dari 23 kabupaten/kota di Provinsi Aceh dan Produk Domestik Regional Bruto Provinsi Aceh tahun 2009-2013. Model analisis yang digunakan adalah model analisis Shift Share dan Pearson Correlation Matrix. Dari hasil analisis Shift Share dan hasil uji Pearson Correlation didapatkan sektor unggulan Kota Sabang mempunyai hubungan yang sangat kuat dengan sektor unggulan Kota Banda Aceh, Kabupaten Aceh Besar, Kabupaten Aceh Jaya, Kabupaten Aceh Barat. Sektor unggulan Kota Banda Aceh mempunyai hubungan yang sangat kuat dengan Kota Sabang, Kabupaten Aceh Besar, dan Kabupaten Aceh Barat. Sektor unggulan Kota Lhokseumawe mempunyai hubungan yang kuat dengan Kabupaten Pidie Jaya, Kabupaten Bener Meriah, dan Kabupaten Aceh Tengah. Sektor unggulan Kota Langsa mempuyai hubungan yang kuat dengan Kabupaten Aceh Tamiang dan Kabupaten Aceh Tenggara. Sektor unggulan Kota Subulussalam mempunyai hubungan yang sangat kuat dengan sektor unggulan Kabupaten Aceh Barat Daya, Kabupaten Aceh Selatan, Kabupaten Aceh Singkil, dan Kabupaten Simeulue.